The Comparative Analysis of Regional Governors’ Approaches to Fostering Inclusive Political Institutions in Post-Euromaidan Donbas - Romanova, Valentyna (Kyiv-Mohyla Law and Politics Journal, 2017)
This study is inspired by a theory-driven expectation of a co-author of Why Nations Fail Daren Acemoglu in regard to fostering inclusive political institutions in post-Euromaidan Ukraine despite the armed conflict in Donbas. I examine how appointing a civil society activist – the one who used to help the Ukrainian Army during the security operation in Donbas – for a position of a regional executive in post-Euromaidan Luhansk oblast affects regional governors’ approaches towards the key conditions of inclusive political institutions: state capacity and power distribution. State capacity, namely its key dimension of monopoly over violence, is operationalized as control over the contact line in the armed conflict in Donbas. Power distribution is operationalized as holding democratic elections. I compare the approaches of three regional executives, including the one who was the civil society activist, towards state capacity and power distribution. I find that appointing the civil society activist for a position of a regional executive in post-Euromaidan Luhansk oblast affects regional governors’ approach towards control over the contact line, but not towards holding democratic elections. The study contributes to literatures on inclusive political institutions by analyzing new empirical data in line with the conceptual framework of Acemoglu and Robinson tailored for its application in post-Euromaidan Luhansk oblast.